Global Analysis of Quorum Sensing Targets in the Intracellular Pathogen Brucella melitensis 16 M - Uzureau, Sophie (American Chemical Society, 2010)
[Image: see text] Many pathogenic bacteria use a regulatory process termed quorum sensing (QS) to produce and detect small diffusible molecules to synchronize gene expression within a population. In Gram-negative bacteria, the detection of, and response to, these molecules depends on transcriptional regulators belonging to the LuxR family. Such a system has been discovered in the intracellular pathogen Brucella melitensis, a Gram-negative bacterium responsible for brucellosis, a worldwide zoonosis that remains a serious public health concern in countries were the disease is endemic. Genes encoding two LuxR-type regulators, VjbR and BabR, have been identified in the genome of B. melitensis 16 M. A ΔvjbR mutant is highly attenuated in all experimental models of infection tested, suggesting a crucial role for QS in the virulence of Brucella. At present, no function has been attributed to BabR. The experiments described in this report indicate that 5% of the genes in the B. melitensis 16 M genome are regulated by VjbR and/or BabR, suggesting that QS is a global regulatory system in this bacterium. The overlap between BabR and VjbR targets suggest a cross-talk between these two regulators. Our results also demonstrate that VjbR and BabR regulate many genes and/or proteins involved in stress response, metabolism, and virulence, including those potentially involved in the adaptation of Brucella to the oxidative, pH, and nutritional stresses encountered within the host. These findings highlight the involvement of QS as a major regulatory system in Brucella and lead us to suggest that this regulatory system could participate in the spatial and sequential adaptation of Brucella strains to the host environment.